The discussion of body in 'Every Day' by David Levithan - Tanuwijaya, Tifanny (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
In the novel Every Day by David Levithan, there exists a profound discussion about body through its protagonist A’s life, its plot, dialogues, and events that unfold. This paper uses qualitative textual analysis as its methods in order to obtain relevant data to be further analyzed using the theoretical framework from Stuart Hall (theory of representation (2013)) and Chris Shilling (The Body and Social Theory (2003)). Through the indexical signs from the text, there are discussions of how the body is represented, which are as something superficial, as a mask, and as something temporary. Through the analysis of the social body, it is also found that the body has become a social asset in which it could also contribute to one’s self-identity, creating the body as a project that one could work on throughout one’s life. Consequently, the metaphor of body as a machine appears, as well as the revelation that there is also a close relation between death and the body. Through death, the social body is reduced into individual body, where the living often avoids the dead, fearing subconsciously of their own. These aspects could be observed from A’s life and Rhiannon’s response towards it.